2016
DOI: 10.1084/jem.20160459
|View full text |Cite
|
Sign up to set email alerts
|

PKA regulatory IIα subunit is essential for PGD2-mediated resolution of inflammation

Abstract: Activation of DP1 by PGD2 in macrophages induces the binding of PRKAR2A to the IFN-γR2 transmembrane region, inhibits JAK2/STAT1 signaling, and triggers the expression of antiinflammatory and reparative genes in myocardial infarction and sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 40 publications
4
59
0
Order By: Relevance
“…We have also reported that DP1 mediates M2 polarization through suppression of the STAT1 pathway and activation of the STAT6 pathway (Kong et al, 2016). Similarly, here we found that niacin pretreatment depressed LPS/IFNg-induced STAT1 activation (Fig.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…We have also reported that DP1 mediates M2 polarization through suppression of the STAT1 pathway and activation of the STAT6 pathway (Kong et al, 2016). Similarly, here we found that niacin pretreatment depressed LPS/IFNg-induced STAT1 activation (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Consistent with this, H-PGDS deficiency results in impaired inflammatory resolution in mice (Rajakariar et al, 2007), and the proresolution effects of PGD 2 are believed to contribute to balancing the secretion of pro-versus antiinflammatory cytokines through the DP1 receptor (Rajakariar et al, 2007). We found that PGD 2 promotes M2 polarization and resolution of acute inflammation, including MI, through DP1-mediated suppression of JAK2-STAT1 signaling (Kong et al, 2016). Interestingly, in vascular inflammation animal models, DP1 activation restrains aneurysm formation in males and atherogenesis in females (Song et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations